2021
DOI: 10.1161/jaha.120.017371
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Morphology, Function, and Hemodynamics in Patients With Morbid Obesity and Nonalcoholic Steatohepatitis

Abstract: Background The patients with nonalcoholic fatty liver disease demonstrate an increased cardiovascular risk. The adverse influence of liver abnormalities on cardiac function are among many postulated mechanisms behind this association. The aim of the study was to evaluate cardiac morphology and function in patients with morbid obesity referred for bariatric surgery with liver biopsy. Methods and Results We evaluated with echocardiography 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Published studies suggest that obesity adversely affects the cardiac structure and LV function before the onset of organic heart disease ( 18 ). A recent study found that NASH patients with extreme obesity were associated with LV concentric remodeling and hyperdynamic circulation ( 29 ). Like them, we have measured the waist circumstance, and subcutaneous fat, and these indicators were significantly higher in the overweight/obesity subgroup; the patterns of fat distribution may be related to the metabolic abnormalities and ectopic deposition of fat in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies suggest that obesity adversely affects the cardiac structure and LV function before the onset of organic heart disease ( 18 ). A recent study found that NASH patients with extreme obesity were associated with LV concentric remodeling and hyperdynamic circulation ( 29 ). Like them, we have measured the waist circumstance, and subcutaneous fat, and these indicators were significantly higher in the overweight/obesity subgroup; the patterns of fat distribution may be related to the metabolic abnormalities and ectopic deposition of fat in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…19 In particular, left ventricular concentric remodeling, which was an unfavorable prognostic sign, was revealed in NASH patients. 20 LF in NASH may also be associated with CVDs by a more expressed profile of systemic inflammation affecting various organs and systems and the interactions between them, leading to further inflammation and immune response activation. 21…”
Section: Pathophysiological Mechanisms Of Cardiovascular Disorders In...mentioning
confidence: 99%
“…66 Patients with extreme obesity and nonalcoholic steatohepatitis demonstrated left ventricular concentric remodeling and hyperdynamic circulation. 67 Furthermore, CRP levels are related to insulin resistance and the presence of metabolic syndromes, especially in women. 68 41 Obesity is associated with higher levels of CRP, with a stronger association in women and North Americans/Europeans, with gender differences only emerging in adulthood.…”
Section: Obesity As An Inflammatory Statementioning
confidence: 99%
“…66 Patients with extreme obesity and nonalcoholic steatohepatitis demonstrated left ventricular concentric remodeling and hyperdynamic circulation. 67 Furthermore, CRP levels are related to insulin resistance and the presence of metabolic syndromes, especially in women. 68…”
Section: Obesity As An Inflammatory Statementioning
confidence: 99%